1988
DOI: 10.1086/132257
|View full text |Cite
|
Sign up to set email alerts
|

On the period and nature of the light and radial-velocity variations of HD 25799

Abstract: Reanalysis of the published radial velocities of the supposed spectroscopic binary HD 25799 shows that its period is 0.9121679 day rather than the 10.67 days found by Blaauw and van Albada (1963). We have obtained new photometric observations of this star during the period 1981-87. Comparison of light curves formed from these observations with each other and with light curves formed from archival data shows that the amplitude and possibly the shape of the light curve are variable. These changes cannot be expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…BvA's discovery of "erratic velocity changes" was in fact the first indication that this object is not a normal binary. Morris et al (1988) showed that an improved ephemeris (notably P = 0.9121679 d) could fit all previous spectroscopic data, but also showed, based on new photometric data, that the object is not a binary but a nonradial pulsator. This finding was confirmed later by Hipparcos photometry.…”
Section: Spectroscopic Binariesmentioning
confidence: 57%
See 1 more Smart Citation
“…BvA's discovery of "erratic velocity changes" was in fact the first indication that this object is not a normal binary. Morris et al (1988) showed that an improved ephemeris (notably P = 0.9121679 d) could fit all previous spectroscopic data, but also showed, based on new photometric data, that the object is not a binary but a nonradial pulsator. This finding was confirmed later by Hipparcos photometry.…”
Section: Spectroscopic Binariesmentioning
confidence: 57%
“…T Morris et al (1988); this is a non-radial pulsator; HD 25833: Giménez & Clausen (1994) (cf. Popper 1974.…”
Section: Hdmentioning
confidence: 99%